2020
DOI: 10.1186/s12860-020-00330-w
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic analysis of Ecm14, a conserved fungal pseudopeptidase

Abstract: Background Like most major enzyme families, the M14 family of metallocarboxypeptidases (MCPs) contains a number of pseudoenzymes predicted to lack enzyme activity and with poorly characterized molecular function. The genome of the yeast Saccharomyces cerevisiae encodes one member of the M14 MCP family, a pseudoenzyme named Ecm14 proposed to function in the extracellular matrix. In order to better understand the function of such pseudoenzymes, we studied the structure and function of Ecm14 in S.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…It contains a prodomain, which can be cleaved by the action of trypsin or chymotrypsin, and a domain with homology to the carboxypeptidase domain, but with a substitution of the general base glutamate for a lysine ( Table 2 ). Likely due to this substitution, no enzymatic activity has been detected, as determined by standard assays ( Figure 1A ) ( McDonald et al, 2020 ). A synthetic lethal screen in the S. cerevisiae system was unable to identify a function ( McDonald et al, 2020 ).…”
Section: M14 Carboxypeptidasesmentioning
confidence: 98%
See 1 more Smart Citation
“…It contains a prodomain, which can be cleaved by the action of trypsin or chymotrypsin, and a domain with homology to the carboxypeptidase domain, but with a substitution of the general base glutamate for a lysine ( Table 2 ). Likely due to this substitution, no enzymatic activity has been detected, as determined by standard assays ( Figure 1A ) ( McDonald et al, 2020 ). A synthetic lethal screen in the S. cerevisiae system was unable to identify a function ( McDonald et al, 2020 ).…”
Section: M14 Carboxypeptidasesmentioning
confidence: 98%
“…Likely due to this substitution, no enzymatic activity has been detected, as determined by standard assays ( Figure 1A ) ( McDonald et al, 2020 ). A synthetic lethal screen in the S. cerevisiae system was unable to identify a function ( McDonald et al, 2020 ). However, other studies have found Ecm14 to be involved in aggregate invasive growth in C. albicans and possibly in invasion by the plant pathogen Verticillium dahlia ( Chow et al, 2019 ; Zhang et al, 2020 ).…”
Section: M14 Carboxypeptidasesmentioning
confidence: 98%